Estudo da eficácia, segurança e tolerabilidade do Brosimum gaudichaudii Trécul em indivíduos adultos portadores de vitiligo - Miranda, Amanda Rodrigues (2014)
Vitiligo is a chronic disease of skin, acquired and idiopathic, characterized by circumscribed depigmented macules or patches. The treatment is still a challenge and don´t have an effective treatment that may improve all patients. The traditional psoralen photosensitizers are options for the treatment of vitiligo. In the Brazilian cerrado is popularly known action of Brosimum gaudichaudii Trécul (BGT), or mamacadela, which is an herbal psoralen. The goal of this study was evaluate the efficacy, safety and tolerability of BGT in adult patients with vitiligo, in topical and systemic presentations. A randomized controlled trial, double-blind and placebo-controlled was conducted. Of the 58 selected patients, 33 were randomized, 17 in the treatment group (G1) and 16 in the placebo group (G2). These remained until the end of the study 10 patients in G1 and G2 in 6 patients. The interventions were 800 mg / day of medication per orally and use of the ointment for 22 weeks, together with graded and daily photoexposure. The effectiveness of the BGT was assessed using the Vitiligo Area Score Index (VASI), applied by a dermatologist at all clinic visits. Already the safety and tolerability were assessed by laboratory tests before and during treatment, and observation of adverse events. All patients were classified with generalized vitiligo. The group that received the medication (G1) improved significantly VASI in intra-group evaluation (p <0.05) and also a higher proportion of repigmentation compared to G2. The VASI don´t have association with the analysis variables (gender, age, skin type, previous treatment, education, emotional stress, time of diagnosis, treatment adherence) (p> 0.05). Adherence to photoexposure was irregular in both groups, and don´t have statistically significant relationship with changes of VASI (p > 0.05). Laboratory tests showed no significant changes. Adverse events were mild and transient and the most common being erythema, and occurred predominantly in G1 patients. Therefore, it can be concluded that the BGT is effective in the treatment of vitiligo, with safe and well tolerated in the long term.